Schlenk's Legacy—Methyllithium Put under Close Scrutiny. Issue 6 (28th December 2022) - Lebon, Jakob; Mortis, Alexandros; Maichle‐Mössmer, Cäcilia; Manßen, Manfred; Sirsch, Peter; Anwander, Reiner
Abstract: Commercially available stock solutions of organolithium reagents are well‐implemented tools in organic and organometallic chemistry. However, such solutions are inherently contaminated with lithium halide salts, which can complicate certain synthesis protocols and purification processes. Here, we report the isolation of chloride‐free methyllithium employing K[N(SiMe3 )2 ] as a halide‐trapping reagent. The influence of distinct LiCl contaminations on the 7 Li‐NMR chemical shift is examined and their quantification demonstrated. The structural parameters of new chloride‐free monomeric methyllithium complex [(Me3 TACN)LiCH3 ], ligated by an azacrown ether, are assessed by comparison with a halide‐contaminated variant and monomeric lithium chloride [(Me3 TACN)LiCl], further emphasizing the effect of halide impurities. Abstract : Halide contaminations of commercial methyllithium solutions (MeLi‐ c ) can be simply removed by the use of K [N (SiMe3 )2 ] as a halide‐trapping reagent and solvent‐dependent precipitation. 7 Li‐NMR spectroscopy is an efficient tool for quantifying the halide contaminations, which can effect solid‐state structures as shown for monomeric [(Me3 TACN)LiCH3 ].